Chlorine trifluoride gas adsorption on the Fe, Ru, Rh, and Ir decorated gallium nitride nanotubes. (15th November 2022) - Bloh, Anmar Hameed; Kadhim, Mustafa M.; Obaid, Rasha Fadhel; Taban, Taleeb Zedan; Hachim, Safa K.; Abdullaha, Sallal A.H.; Almashhadani, Haider Abdulkareem; Y., Anshul
Abstract: The impact of decorating Fe, Ru, Rh, and Ir metals upon the sensing capability of a gallium nitride nanotube (GaNNT) in detecting chlorine trifluoride (CT) was scrutinized using the density functionals B3LYP and B97D. The interaction of the pristine GaNNT with CT was a physical adsorption with the sensing response (SR) of approximately 6.9. After decorating the above-mentioned metals on the GaNNT, adsorption energy of CT changed from −5.8 to −18.6, −18.9, −19.4, and −20.1 kcal/mol by decorating the Fe, Ru, Rh, and Ir metals into the GaNNT surface, respectively. Also, the corresponding SR dramatically increased to 39.6, 52.3, 63.8, and 106.6. This shows that the sensitivity of the metal-decorated GaNNT (metal@GaNNT) increased by increasing the atomic number of metals. As energy decomposition analysis revealed, the electrostatic, also known as cation-lone pair interaction, was mostly the nature of the interaction between the CT and metal@GaNNT. Highlights: Fe, Ru, Rh, and Ir-decorated GaN nanotube may be highly sensitive ClF3 sensor. The sensing response significantly rises 106.6 by Ir decoration. A short recovery time of 4.4 s is found for the ClF3 desorption from Ir-decorated GaN.